A method for powering an internet of things node based on a perovskite solar cell

CN122909991APending Publication Date: 2026-10-13DALIAN TITANIUM LIGHT TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611187124.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种基于钙钛矿太阳能电池的物联网节点供能方法,解决了现有柔性光伏节点在集成制造时会产生应力裂纹与热损伤,且在弱光临界电压下会频繁死机重启的问题

Benefits of technology

1、本发明在刚性载板和柔性聚酰亚胺基底之间引入由端乙烯基聚二甲基硅氧烷交联制备的弹性缓冲层,由于硅氧烷交联网络固化后的弹性模量偏低,能够吸收后续磁控溅射和热处理加工中产生的部分残余应力,使得柔性薄膜在加工受力时不会产生内部微裂纹,改善柔性节点器件整体的制造良率与结构稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122909991A_ABST
    Figure CN122909991A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of Internet of Things micro energy, and discloses a method for supplying energy to an Internet of Things node based on a perovskite solar cell, which comprises the following steps: heating and curing end-vinyl polydimethylsiloxane and a crosslinking agent into an elastic buffer layer, and attaching a polyimide film to the surface to form a composite carrier plate for absorbing residual stress generated during processing; after preparing and patterning etching a bottom electrode, spin-coating a precursor solution on the surface of the substrate and annealing to generate a perovskite photosensitive layer; completing local packaging in cooperation with two side transport layers and an inorganic water-blocking layer; and in the assembly stage, using low-temperature curing silver paste to attach and connect power management chips and other components, and avoiding the heat degradation interval of photoelectric materials in a mild curing environment. The application introduces a stop power supply threshold, a restart threshold and a voltage back difference control logic at the circuit end, so that the microcomputer automatically switches between sleep, frequency reduction and operation according to the energy storage voltage, thereby relieving the problem of frequent restart of the node device under weak light critical voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of IoT micro-energy technology, specifically to a method for powering IoT nodes based on perovskite solar cells. Background Technology

[0002] With the rollout of IoT technology, the number of wireless sensor nodes deployed in various environments is gradually increasing. Traditional battery power supply can hardly meet the needs of long-term maintenance-free use. Utilizing ambient light energy for self-powering has become a way to solve the problem of node endurance. Perovskite solar cells have high photoelectric conversion efficiency and can be adapted to various mounting surfaces when combined with flexible substrates. Therefore, they are often used as micro energy modules for IoT devices.

[0003] In practical fabrication and application scenarios, the system integration of flexible perovskite power supply devices faces some engineering challenges. When the flexible substrate undergoes processing steps such as electrode sputtering and various thin film heat treatments, residual stress accumulates inside, causing the substrate to deform. This leads to microcracks in the brittle semiconductor thin film, reducing the overall yield of photovoltaic devices. To form a complete power supply node, power management chips, communication modules, and energy storage elements need to be directly integrated onto the photovoltaic substrate. Conventional electronic component surface mount packaging often uses reflow soldering or medium-high temperature curing of conductive adhesives. The temperature exceeds the thermal stability limit of perovskite materials, causing thermal degradation of the bottom photoelectric conversion layer during the assembly stage.

[0004] In addition, at the electrical operation level, due to the frequent fluctuations in ambient light intensity, the energy acquired by the nodes is not stable. When the environment is under low light conditions and the internal energy storage voltage just reaches the microprocessor's startup threshold, once the system is woken up and connected to the communication load, the transient high current consumption will quickly lower the bus voltage, directly triggering undervoltage power failure. The frequent crashes and repeated restarts at the critical voltage not only waste the already meager acquisition power, but also make it difficult for the nodes to accumulate enough energy to complete a complete data transmission. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for powering IoT nodes based on perovskite solar cells, which solves the problems of stress cracks and thermal damage that occur during the integration and manufacturing of existing flexible photovoltaic nodes, as well as frequent crashes and restarts under weak light critical voltage.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for powering Internet of Things (IoT) nodes based on perovskite solar cells, the method comprising the following steps: Vinyl-terminated polydimethylsiloxane and polymethylhydrosiloxane crosslinking agent are mixed, degassed, coated onto a carrier plate, and heated and cured to obtain a polydimethylsiloxane elastic buffer layer. A flexible polyimide film is attached to the surface of the elastic buffer layer and vacuum laminated and pressurized to obtain a composite carrier plate that provides flexible buffer support. A metal adhesion layer and a copper layer are sequentially deposited by magnetron sputtering on the surface of a composite substrate. The exposed copper layer and the bottom metal adhesion layer are patterned and stripped by photolithography and wet etching processes to obtain the bottom electrode. A hole transport layer is spin-coated outside the installation area. A perovskite precursor solution composed of lead iodide, methyl ammonium iodide and a mixed solvent is spin-coated and annealed to form a perovskite layer. An electron transport layer, a buffer layer and a silver electrode are then prepared in sequence. An inorganic water-barrier oxygen layer is deposited using atomic layer deposition technology to encapsulate the photovoltaic area. A low-temperature curing silver paste containing flake-shaped micron silver powder and an organic carrier is used to place the power management chip, button-type double-layer supercapacitor, and IoT communication module on the corresponding pads to complete the electrical connection and thermal curing. The output of the perovskite solar cell is connected to the input of the power management chip. The state control logic is configured, and a first set threshold, a second set threshold, a power stop threshold, and a restart threshold are set. Combined with the voltage hysteresis set by the system, the operation and sleep modes of the 32-bit ultra-low power single-chip microcomputer are automatically switched to avoid frequent restarts of IoT nodes under critical voltage, thus achieving all-weather self-sustaining power supply.

[0007] When heated, the terminal vinyl groups in the matrix and the silane-hydrogen bonds in the crosslinking agent undergo addition curing to form a crosslinked polymer network. At this time, the material is in a state of low elastic modulus. The buffer layer is inserted between the rigid carrier plate and the flexible polyimide film, which can absorb the residual stress brought by the magnetron sputtering and heat treatment process. This helps to maintain the flatness of the flexible substrate, thereby reducing the generation of microcracks inside the thin-film battery to a certain extent.

[0008] By using a prepared low-temperature curing silver paste in conjunction with a pre-set photolithographic bottom electrode, power management chips and other components are fixed in their corresponding positions. Since the curing temperature window of the silver paste is below the thermal degradation critical point of the perovskite material, the integration of the photovoltaic power supply and control circuit can be completed without significantly damaging the thermistor layer.

[0009] By widening the gap between the power outage threshold and the restart threshold, a voltage hysteresis is formed on the charge and discharge curve. When unstable lighting causes the energy storage voltage to hover at the critical point, the hysteresis setting can intercept repeated restarts caused by the bus voltage drop due to the instantaneous connection of the load, so as to ensure that the communication module is powered on before completing a data transmission.

[0010] Preferably, the polydimethylsiloxane elastic buffer layer comprises the following components in parts by weight: 100 to 150 parts of vinyl-terminated polydimethylsiloxane; and 8 to 10 parts of polymethylhydrosiloxane crosslinking agent. The steps of mixing the vinyl-terminated polydimethylsiloxane and the polymethylhydrosiloxane crosslinking agent, degassing, coating onto a carrier plate, and heating to cure, to obtain the polydimethylsiloxane elastic buffer layer, and then attaching a flexible polyimide film to the surface of the elastic buffer layer and performing vacuum lamination and pressure holding, to obtain a composite carrier plate providing flexible buffer support, include: stirring at 500 to 800 rpm for 10 to 20 min, followed by degassing at a vacuum of -0.10 to -0.08 MPa for 15 to 30 min; controlling the coating film thickness to be 100 to 500 μm, curing at 80 to 100°C for 30 to 60 min; and holding under an ambient pressure of 50 to 90 Pa and a film pressure of 0.2 to 0.5 MPa for 10 to 15 min.

[0011] By adopting technical solutions, the amount of crosslinking agent is set in conjunction with the curing temperature, and the crosslinking density of the material is adjusted to meet the elastic recovery requirements. The vacuum degassing operation during processing removes most of the air bubbles in the resin mixture, which reduces the local strain caused by the expansion of air bubbles during subsequent lamination heating. At the same time, the set film thickness allowance leaves room for deformation, which helps to buffer the mechanical pressure generated during the lamination operation.

[0012] Preferably, the perovskite precursor solution is prepared from the following components in parts by weight: 46.1 parts lead iodide; 15.9 to 16.7 parts methylammonium iodide; 56.6 to 62.9 parts N,N-dimethylformamide; and 7.4 to 18.4 parts dimethyl sulfoxide. A hole transport layer is spin-coated outside the mounting area. The perovskite precursor solution, composed of lead iodide, methylammonium iodide, and a mixed solvent, is spin-coated and annealed to form a perovskite layer. An electron transport layer, a buffer layer, and a silver electrode are then sequentially prepared. An inorganic water-barrier oxygen layer is deposited using atomic layer deposition (ALD) technology for the photovoltaic region. The encapsulation steps of the domain include: when preparing the perovskite precursor solution, the lead ion concentration of the system is controlled to be 1.2 to 1.5 mol / L, and the solution is continuously magnetically stirred at 60°C for 2 to 4 h and then filtered for separation; the perovskite precursor solution is spin-coated at a speed of 4000 to 6000 rpm, and 100 to 200 μL of chlorobenzene is added dropwise at the center at the 10th to 15th second, followed by isothermal annealing at 100 to 110°C for 10 to 30 min; and an inorganic water-barrier oxygen layer with a thickness of 20 to 50 nm is deposited at a temperature of 80 to 100°C.

[0013] By employing a technical solution, N,N-dimethylformamide and dimethyl sulfoxide are used to form a composite solvent system. Dimethyl sulfoxide contains oxygen atoms that exhibit Lewis basicity, which will undergo a coordination complexation reaction with lead iodide, which has Lewis acidity, to generate an intermediate complex. This slows down the crystallization rate during the early spin coating process. When a nonpolar chlorobenzene antisolvent is added, the surface solvent is quickly carried away, and the liquid film enters a highly supersaturated state and begins to nucleate in large quantities. Subsequent thermal annealing causes the complex to decompose and remove the dimethyl sulfoxide, ultimately leaving a polycrystalline film with relatively good crystal quality.

[0014] Preferably, the low-temperature curing silver paste is made from the following components in parts by weight: 70 to 85 parts of flake-shaped micron-sized silver powder; 15 to 30 parts of an organic carrier; wherein the organic carrier is composed of epoxy resin and an amine curing agent. The steps of using the low-temperature curing silver paste containing flake-shaped micron-sized silver powder and an organic carrier to place a power management chip, a button-type double-layer supercapacitor, and an IoT communication module onto corresponding pads to complete electrical connections and thermal curing include: preparing the low-temperature curing silver paste through grinding and dispersion treatment, controlling the viscosity at room temperature to be 20 to 40 Pa·s; and heating and curing at 60 to 80°C for 30 to 60 minutes.

[0015] By adopting a technical solution, the silver powder content in the selected range just exceeds the conductivity percolation threshold. Under a mild heating environment, the active hydrogen of the curing agent causes the epoxy groups to open the ring and crosslink. When the resin network is cured and shrinks, it generates internal pressure, which squeezes the dispersed micron silver powder together to form a conductive network. This relatively low curing temperature will not cause the perovskite material to degrade due to heat, thereby reducing the risk of thermal damage during component assembly.

[0016] Preferably, the metal adhesion layer is a titanium layer or a chromium layer; the hole transport layer is an annealed PTAA film; the electron transport layer is a PCBM film; the buffer layer is a thermally evaporated BCP film; and the inorganic water-blocking oxygen layer is an aluminum oxide film.

[0017] By employing technical solutions, the titanium or chromium layer combines with the polar groups on the surface of the flexible substrate, increasing the adhesion of the bottom electrode. The energy levels of the PTAA and PCBM films match the valence band and conduction band of the perovskite, respectively, facilitating the extraction of charge to both sides. The BCP layer acts as a hole blocker, slowing down nonradiative recombination at the interface. The outer alumina layer is mainly used to block external moisture and delay the failure of perovskite materials due to moisture.

[0018] Preferably, the output terminal of the perovskite solar cell is connected to the input terminal of the power management chip, and state control logic is configured to set a first set threshold, a second set threshold, a power supply stop threshold, and a restart threshold. Combined with the voltage hysteresis set by the system, the operating and sleep modes of the 32-bit ultra-low-power single-chip microcomputer are automatically switched to avoid frequent restarts of IoT nodes under critical voltage conditions. The steps to achieve all-weather self-sustaining power supply include: The system is configured with a first set threshold of 3.0 to 3.3V, a second set threshold of 2.6 to 2.9V, a power-off threshold of 2.2 to 2.3V, and a restart threshold of 2.6 to 2.8V, corresponding to a system-set voltage hysteresis of 0.3 to 0.6V. When the power supply voltage is higher than the first set threshold, it operates at full power or performs data acquisition and transmission at the set frequency. When the power supply voltage is between the second and first set thresholds, it operates at a reduced frequency. When the power supply voltage is lower than the power-off threshold, the 32-bit ultra-low power single-chip microcomputer enters undervoltage sleep or deep sleep. When the light source is restored and the power supply voltage rises above the restart threshold, the 32-bit ultra-low power single-chip microcomputer is reawakened and the load is connected.

[0019] By adopting technical solutions, the power supply system is divided into management rules according to different voltage ranges. When the light is extremely poor, the system enters sleep mode to reduce leakage. When the power recovers, the set voltage difference of 0.3 to 0.6V is equivalent to a buffer power pool. The extra power is sufficient to cope with the consumption required for the microcontroller's cold start and sending one data. It will not directly trigger a power outage due to the voltage drop caused by a large current. When it is in the intermediate critical state, it switches to frequency reduction operation, which also helps to control power consumption and maintain energy balance.

[0020] This invention provides a method for powering Internet of Things (IoT) nodes based on perovskite solar cells. It offers the following advantages: 1. The present invention introduces an elastic buffer layer prepared by crosslinking vinyl-terminated polydimethylsiloxane between a rigid carrier plate and a flexible polyimide substrate. Since the elastic modulus of the siloxane crosslinked network after curing is relatively low, it can absorb some of the residual stress generated during subsequent magnetron sputtering and heat treatment, so that the flexible film will not generate internal microcracks when subjected to processing stress, thereby improving the overall manufacturing yield and structural stability of the flexible node device.

[0021] 2. Considering that perovskite materials are relatively sensitive to temperature, this invention uses flake-shaped micron-sized silver powder combined with epoxy resin system to form a low-temperature curing silver paste to connect power management chips and other circuit components. The curing temperature of the silver paste is controlled at around 60 to 80°C, avoiding the temperature range in which the perovskite crystal structure begins to undergo thermal degradation. This reduces the probability of semiconductor layer performance damage caused by heating and curing while completing the physical integration of the photovoltaic power supply end and the computing and communication unit.

[0022] 3. In terms of power supply control strategy, this invention sets a voltage hysteresis of 0.3 to 0.6V in the system by widening the gap between the power supply stop threshold and the restart threshold. When the node energy storage voltage hovers at the critical working state in a low light environment, the voltage difference is equivalent to leaving a part of the reserve power space. The reserved power can cover the energy consumed by the microcontroller to wake up and send data once, avoiding the communication module from being triggered by a sudden voltage drop as soon as the load is connected, thus alleviating the problem of repeated crashes and restarts of node devices under critical voltage. Attached Figure Description

[0023] Figure 1 This is a graph showing the IV and PV characteristics of the perovskite solar cell under simulated illumination in Example 1 of the present invention. Figure 2 This is a voltage-time curve of the button-type double-layer supercapacitor in Embodiment 1 of the present invention during the charging process; Figure 3 This is a voltage waveform diagram showing the evolution of the system bus voltage over time with simulated illumination environment in Embodiment 1 of the present invention; Figure 4 This is a waveform diagram of the current pulse of the radio frequency transmitting antenna of the wireless communication module in Embodiment 1 of the present invention; Figure 5 This is a comparison chart of the IV characteristic curves of the perovskite solar cell regions in Embodiment 1 of the present invention and various comparative examples under simulated illumination conditions; Figure 6 This is a bar chart comparing the insulation impedance between key data bus pins of nodes in Embodiment 1 of the present invention and various comparative examples; Figure 7 This is a graph showing the peel strength-displacement relationship between Example 2 and Comparative Example 4 of the present invention in a 90-degree peel test; Figure 8 This is a scatter plot of the sheet resistance of the test area after etching in Embodiment 2 and Comparative Example 4 of the present invention. Figure 9 The following are graphs showing the evolution of system bus voltage versus time during 3 hours of continuous operation for Embodiment 3 and the comparative examples of the present invention. Figure 10 The chart shows the number of abnormal resets and the data packet transmission success rate of the 32-bit ultra-low power single-chip microcomputer during the testing period for Embodiment 3 and the comparative examples of the present invention. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0026] The base polymer of polydimethylsiloxane is vinyl-terminated polydimethylsiloxane, CAS number 68083-19-2; The polydimethylsiloxane crosslinking agent is polymethylhydrosiloxane, CAS number 63148-57-2; The polyimide film is formed by the polycondensation of pyromellitic dianhydride and diamine monomers, with a crystallinity of less than 10% and a density of 1.42 g / cm³. 3 The thickness ranges from 25μm to 125μm, and the coefficient of thermal expansion is less than 20ppm / ℃ in the range of 20℃ to 200℃.

[0027] The hole transport material is poly(4-phenyl)(2,4,6-trimethylphenyl)amine, chemically abbreviated as PTAA, CAS number 1333317-99-9.

[0028] The precursor materials for perovskite photovoltaic functional layers include lead iodide (CAS number 10101-63-0) and methylammonium iodide (CAS number 14965-49-2). The electron transport material is methyl [6,6]-phenyl-C61-butyrate, chemically abbreviated as PCBM, and CAS number 160848-22-6; The hole-blocking material is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, chemically abbreviated as BCP, and CAS number 4733-39-5.

[0029] The UV-curable epoxy resin used for encapsulation is a mixture of alicyclic epoxy resin and bisphenol A type epoxy resin, with a viscosity of 300 mPa·s to 500 mPa·s at 25°C and a curing shrinkage rate of less than 2%. The polyethylene terephthalate water-blocking film has a thickness of 50 μm and a dense silica water-blocking and oxygen-blocking layer with a thickness of 200 nm on its surface. The anisotropic conductive film is composed of an epoxy resin substrate with a thickness of 15μm to 25μm and gold-plated polymer conductive particles with a diameter of 3μm to 5μm, and the minimum hot-press curing temperature is 80℃. The low-temperature curing silver paste is composed of 70wt% to 85wt% flake-shaped micron silver powder and 15wt% to 30wt% epoxy resin and amine curing agent. The viscosity is 20Pa·s to 40Pa·s at 25℃ and the volume resistivity is less than 0.0001Ω·cm after complete curing. The energy storage module uses a button-type double-layer supercapacitor with a rated operating voltage of 5.5V and a nominal capacitance of 0.1F to 0.47F, and an equivalent series resistance of less than 50Ω. The microcontroller is a 32-bit ultra-low-power single-chip microcomputer with a deep sleep current of less than 0.5μA.

[0030] In this invention, the units of measurement for all materials and solvents are uniformly referred to as parts by weight.

[0031] Example 1: This embodiment provides a method for powering Internet of Things (IoT) nodes based on perovskite solar cells, including the following steps: S1. Add 100 parts of vinyl-terminated polydimethylsiloxane and 8 parts of polymethylhydrosiloxane crosslinking agent to a mixing tank, stir at 650 rpm for 15 min in a vacuum mixer, and then degas for 20 min under a vacuum of -0.09 MPa. Coat the degassed mixture onto a cleaned and dried flat alkali-free glass substrate, control the liquid film thickness to 300 μm with a scraper, and heat and cure in a 90℃ oven for 45 min to obtain a polydimethylsiloxane elastic buffer layer. Select a 75 μm thick polyimide film as a flexible substrate, and use a pressing roller to flatly attach the polyimide film to the surface of the polydimethylsiloxane elastic buffer layer under a pressure of 0.3 MPa. Place it in a vacuum laminator and hold it under an ambient pressure of 80 Pa for 12 min.

[0032] S2. Place the composite substrate in the magnetron sputtering system and evacuate the cavity to 8.0 × 10⁻⁶. -4 The working pressure was stabilized at 0.15 Pa by introducing high-purity argon gas. A 30 nm thick titanium layer was deposited as a metal adhesion layer at 80 W sputtering power, maintaining vacuum without breakage. A 1000 nm thick copper layer was deposited at 135 W power. Positive photoresist was spin-coated onto the copper layer to a thickness of 2.0 μm. The layer was pre-baked at 100 °C for 90 s and then subjected to UV light at 365 nm with a photomask at 150 mJ / cm². 2 Energy exposure, development for 60 seconds, rinsing, hardening and baking at 115°C, wet etching of the exposed copper layer at 45°C using acidic copper chloride etchant, removal of the bottom titanium adhesion layer with 1.5% hydrofluoric acid, and finally ultrasonic stripping of the photoresist and drying.

[0033] S3. The mounting area of ​​electronic components was masked with polytetrafluoroethylene solvent-resistant tape. A PTAA toluene solution with a concentration of 2.0 mg / mL was spin-coated and annealed at 105 °C for 12 min to obtain a hole transport layer. 46.1 parts of lead iodide and 16.2 parts of methyl ammonium iodide were mixed evenly with a molar ratio of approximately 1:1.02. The mixture was added to a mixed solvent consisting of 60.6 parts of N,N-dimethylformamide and 10.9 parts of dimethyl sulfoxide with a weight ratio of approximately 6.5:1. The lead ion concentration of the system was controlled to be 1.35 mol / L. The mixture was continuously magnetically stirred on a constant temperature heating stage at 60 °C for 3 h. The perovskite precursor solution was obtained by filtration using a polytetrafluoroethylene filter with a pore size of 0.22 μm. The perovskite precursor solution was spin-coated at 5000 rpm, and 150 μL of chlorobenzene was added to the center at 12 s. Then, it was annealed at 105 ℃ for 20 min. A PCBM solution with a concentration of 20 mg / mL was spin-coated sequentially. An 8 nm BCP layer and a 100 nm silver electrode were deposited by thermal evaporation. A 30 nm inorganic water-blocking oxygen layer of alumina was deposited at 90 ℃ using atomic layer deposition technology. The polytetrafluoroethylene masking layer was removed. UV-curable epoxy resin was applied to the photovoltaic area and a polyethylene terephthalate water-blocking film was attached. The area was then cured by irradiation with 365 nm UV light for 45 s.

[0034] S4. Take 78 parts of flake-shaped micron silver powder and 22 parts of organic carrier composed of epoxy resin and amine curing agent, and perform homogenization dispersion treatment in a three-roll mill. Control the viscosity at room temperature to 30 Pa·s to prepare low-temperature curing silver paste. Place the power management chip, the 0.22F coin double-layer supercapacitor, the data processing module and the wireless communication module on the corresponding pads, complete the electrical connection with low-temperature curing silver paste, and cure in an environment of 70℃ for 45 min.

[0035] S5. Connect the output of the perovskite solar cell to the input of the power management chip, configure the state control logic, set the first threshold to 3.1V, the second threshold to 2.8V, the power supply stop threshold to 2.3V, and the restart threshold to 2.7V. At this time, the voltage hysteresis is 0.4V. When the voltage is higher than 3.1V, the set frequency data acquisition and transmission are executed; when it is between 2.8V and 3.1V, the frequency is reduced; when it is lower than 2.3V, the 32-bit ultra-low power single-chip microcomputer is in deep sleep; when the voltage rises back to above 2.7V after the light recovers, the load is reconnected. Through configuration, under ambient light conditions, the perovskite solar cell stably outputs electrical energy and stores it in the coin double-layer supercapacitor. Combined with the state control logic, the IoT node can be successfully powered 24 / 7 without external power connection.

[0036] Example 2: This embodiment provides a method for powering Internet of Things (IoT) nodes based on perovskite solar cells, including the following steps: S1. Add 100 parts of vinyl-terminated polydimethylsiloxane and 10 parts of polymethylhydrosiloxane crosslinking agent to a mixing tank, stir at 500 rpm for 10 min in a vacuum mixer, and then degas for 15 min under a vacuum of -0.08 MPa. Coat the degassed mixture onto a cleaned and dried flat alkali-free glass substrate, control the liquid film thickness to 100 μm with a scraper, and heat and cure in an 80℃ oven for 60 min to obtain a polydimethylsiloxane elastic buffer layer. Select a 25 μm thick polyimide film as a flexible substrate, and use a pressing roller to flatly attach the polyimide film to the surface of the polydimethylsiloxane elastic buffer layer under a pressure of 0.2 MPa. Place it in a vacuum laminator and hold it under an ambient pressure of 50 Pa for 10 min.

[0037] S2. Place the composite substrate in the magnetron sputtering system and evacuate the cavity to 8.0 × 10⁻⁶. -4 The working pressure was stabilized at 0.1 Pa by introducing high-purity argon gas. A 10 nm thick titanium layer was deposited as a metal adhesion layer at a sputtering power of 50 W, maintaining vacuum without breakage. A 500 nm thick copper layer was deposited at a power of 120 W. Positive photoresist was spin-coated onto the copper layer to a thickness of 1.5 μm. The layer was pre-baked at 90 °C for 60 s and then subjected to UV light at 365 nm with a photomask at 100 mJ / cm². 2 Energy exposure, development for 45 seconds, rinsing and hardening baking at 110°C, wet etching of the exposed copper layer using acidic copper chloride etchant at 40°C, removal of the bottom titanium adhesion layer with 1.0% dilute hydrofluoric acid, and finally ultrasonic stripping of the photoresist and drying.

[0038] S3. The mounting area of ​​electronic components was masked with polytetrafluoroethylene solvent-resistant tape. A PTAA toluene solution with a concentration of 1.5 mg / mL was spin-coated and annealed at 100℃ for 10 min to obtain a hole transport layer. 46.1 parts of lead iodide and 15.9 parts of methyl ammonium iodide were mixed evenly with a molar ratio of 1:1. The mixture was added to a mixed solvent composed of 62.9 parts of N,N-dimethylformamide and 18.4 parts of dimethyl sulfoxide with a weight ratio of 4:1. The lead ion concentration of the system was controlled to be 1.2 mol / L. The mixture was continuously magnetically stirred on a constant temperature heating stage at 60℃ for 2 h. The perovskite precursor solution was obtained by filtration using a polytetrafluoroethylene filter with a pore size of 0.22 μm. The perovskite precursor solution was spin-coated at 4000 rpm, and 100 μL of chlorobenzene was added to the center at the 10th second. Then, it was annealed at a constant temperature of 100℃ for 10 min. A PCBM solution with a concentration of 15 mg / mL was spin-coated sequentially. A 5 nm BCP layer and an 80 nm silver electrode were deposited by thermal evaporation. A 20 nm alumina inorganic water-blocking oxygen layer was deposited at 80℃ using atomic layer deposition technology. The polytetrafluoroethylene masking layer was removed. UV-curable epoxy resin was applied to the photovoltaic area and a polyethylene terephthalate water-blocking film was attached. The area was then cured by irradiation with 365 nm UV light for 30 s.

[0039] S4. Take 70 parts of flake-shaped micron silver powder and 30 parts of organic carrier composed of epoxy resin and amine curing agent, and perform homogenization and dispersion treatment in a three-roll mill. Control the viscosity at room temperature to 20 Pa·s to prepare low-temperature curing silver paste. Place the power management chip, the 0.1F coin double-layer supercapacitor, the data processing module and the wireless communication module on the corresponding pads, complete the electrical connection with low-temperature curing silver paste, and cure in an environment of 60℃ for 30 min.

[0040] S5. Connect the output of the perovskite solar cell to the input of the power management chip, configure the state control logic, set the first threshold to 3.0V, the second threshold to 2.6V, the power supply stop threshold to 2.3V, and the restart threshold to 2.6V. At this time, the voltage hysteresis is strictly equal to the lower limit of 0.3V. When the voltage is higher than 3.0V, it runs at full power; when it is between 2.6V and 3.0V, it runs at reduced frequency; when it is lower than 2.3V, the 32-bit ultra-low power single-chip microcomputer enters undervoltage sleep mode; when the light recovers and the voltage rises back to 2.6V, the 32-bit ultra-low power single-chip microcomputer is reawakened. Through configuration, in low light environment, the perovskite solar cell collects light energy, and the system automatically switches between operation and sleep modes according to the voltage threshold, successfully realizing long-term stable power supply of IoT nodes with ultra-low power consumption.

[0041] Example 3: This embodiment provides a method for powering Internet of Things (IoT) nodes based on perovskite solar cells, including the following steps: S1. Add 150 parts of vinyl-terminated polydimethylsiloxane and 10 parts of polymethylhydrosiloxane crosslinking agent to a mixing tank and stir at 800 rpm for 20 min in a vacuum mixer. Then degas at -0.1 MPa for 30 min. Coat the degassed mixture onto a cleaned and dried flat alkali-free glass substrate. Control the liquid film thickness to 500 μm using a scraper. Heat and cure in a 100℃ oven for 30 min to obtain a polydimethylsiloxane elastic buffer layer. Select a 125 μm thick polyimide film as a flexible substrate. Use a pressing roller to flatly attach the polyimide film to the surface of the polydimethylsiloxane elastic buffer layer under a pressure of 0.5 MPa. Place it in a vacuum laminator and hold it under an ambient pressure of 90 Pa for 15 min.

[0042] S2. Place the composite substrate in the magnetron sputtering system and evacuate the cavity to 8.0 × 10⁻⁶. -4 The working pressure was stabilized at 0.2 Pa by introducing high-purity argon gas. A 50 nm thick chromium layer was deposited as a metal adhesion layer at 100 W sputtering power, maintaining vacuum without breakage. A 2000 nm thick copper layer was deposited at 150 W power. Positive photoresist was spin-coated onto the copper layer to a thickness of 3.0 μm. The layer was pre-baked at 110 °C for 120 s and then subjected to UV light at 365 nm with a photomask at 200 mJ / cm². 2 Energy exposure, development for 90 seconds, rinsing, hardening and baking at 120°C, wet etching of the exposed copper layer using acidic copper chloride etchant at 50°C, removal of the bottom chromium adhesion layer using cerium ammonium nitrate etchant, and finally ultrasonic stripping of the photoresist and drying.

[0043] S3. The mounting area of ​​electronic components was masked with polytetrafluoroethylene solvent-resistant tape. A PTAA toluene solution with a concentration of 3.0 mg / mL was spin-coated and annealed at 110℃ for 15 min to obtain a hole transport layer. 46.1 parts of lead iodide and 16.7 parts of methyl ammonium iodide were mixed evenly with a molar ratio of approximately 1:1.05. The mixture was added to a mixed solvent consisting of 56.6 parts of N,N-dimethylformamide and 7.4 parts of dimethyl sulfoxide with a weight ratio of 9:1. The lead ion concentration of the system was controlled to be 1.5 mol / L. The mixture was continuously magnetically stirred on a constant temperature heating stage at 60℃ for 4 h. The perovskite precursor solution was obtained by filtration using a polytetrafluoroethylene filter with a pore size of 0.22 μm. The perovskite precursor solution was spin-coated at 6000 rpm, and 200 μL of chlorobenzene was added to the center at 15 s. Then, it was annealed at 110 ℃ for 30 min. A PCBM solution with a concentration of 25 mg / mL was spin-coated sequentially. A 10 nm BCP layer and a 120 nm silver electrode were deposited by thermal evaporation. A 50 nm inorganic water-blocking oxygen layer of alumina was deposited at 100 ℃ using atomic layer deposition technology. The polytetrafluoroethylene masking layer was removed. UV-curable epoxy resin was applied to the photovoltaic area and a polyethylene terephthalate water-blocking film was attached. The area was then cured by irradiation with 365 nm UV light for 60 s.

[0044] S4. Take 85 parts of flake-shaped micron silver powder and 15 parts of organic carrier composed of epoxy resin and amine curing agent, and perform homogenization and dispersion treatment in a three-roll mill. Control the viscosity at room temperature to 40 Pa·s to prepare low-temperature curing silver paste. Place the power management chip, the 0.47F coin double-layer supercapacitor, the data processing module and the wireless communication module on the corresponding pads, complete the electrical connection with low-temperature curing silver paste, and cure in an 80℃ environment for 60 min.

[0045] S5. Connect the output of the perovskite solar cell to the input of the power management chip, configure the state control logic, set the first threshold to 3.3V, the second threshold to 2.9V, the power supply stop threshold to 2.2V, and the restart threshold to 2.8V. At this time, the voltage hysteresis is 0.6V. When the voltage is higher than 3.3V, it will run at full power; when it is between 2.9V and 3.3V, it will run at reduced frequency; when it is lower than 2.2V, the 32-bit ultra-low power single-chip microcomputer will enter undervoltage sleep mode; when the voltage rises back to above 2.8V after the light recovers, the load will be reawakened. Through configuration, the perovskite solar cell and the coin double-layer supercapacitor work together to avoid frequent restarts of IoT nodes under critical voltage by using the set voltage hysteresis, thus achieving safe and reliable independent micro-energy supply.

[0046] Comparative Example 1: Compared with Example 1, the difference lies in reversing the preparation sequence of S3 and S4. That is, the electronic components are first soldered at high temperature using solder paste on a flexible substrate, and then the perovskite precursor solution is spin-coated and annealed. All other steps are the same.

[0047] Comparative Example 2: Compared with Example 1, the difference is that in S4, instead of using low-temperature curing silver paste, conventional tin-silver-copper lead-free solder paste with a melting point of 217°C is used, and electronic components are connected by reflow soldering at 250°C. All other aspects are the same.

[0048] Comparative Example 3: Compared with Example 1, the difference is that in S3, the electronic component mounting area was not masked with polytetrafluoroethylene solvent-resistant tape, and the perovskite precursor solution was directly spin-coated; otherwise, they are the same.

[0049] Comparative Example 4: Compared with Example 2, the difference is that in S2, the operation of depositing a 10nm thick titanium layer as a metal adhesion layer at a sputtering power of 50W is removed, and a 500nm copper layer is directly deposited on the surface of the polyimide film and then etched. All other aspects are the same.

[0050] Comparative Example 5: Compared with Example 3, the difference is that in S5, the state control logic is modified, the power supply stop threshold is set to 2.2V, the restart threshold is also set to 2.2V, that is, the voltage hysteresis is 0V, and the rest are the same.

[0051] Comparative Example 6: Compared with Example 3, the difference is that in S5, the state control logic is modified, and the power supply stop threshold is set to 2.2V and the restart threshold is set to 2.3V. At this time, the voltage hysteresis is only 0.1V, which does not meet the lower limit value required by Example 3. All other aspects are the same.

[0052] Test Example 1: The complete system prepared in Example 1 was fixed on an optical testing platform. The position of the standard solar simulator light source was adjusted so that the light spot covered the perovskite solar cells on the surface of the system. The light intensity was calibrated to 100 mW / cm² using a standard silicon cell. 2 .

[0053] Using a miniature probe station and conductive clamps, the positive and negative output leads of the system's perovskite solar cell are connected to the input channel of a digital source meter. The voltage scan range is set to -0.1V to 1.2V, and the scan rate is 50mV / s.

[0054] Start the standard solar simulator, perform voltage scanning and record the output current of the corresponding nodes, and simultaneously calculate the output power in the host computer to obtain the IV characteristic curve and PV characteristic curve of the perovskite solar cell.

[0055] Disconnect the source meter to restore electrical continuity between the output terminal of the perovskite solar cell and the input terminal of the power management chip inside the system.

[0056] Connect the voltage test probes of a high-precision multimeter in parallel to the two ends of the button-type double-layer supercapacitor in the system, and set the sampling frequency of the multimeter to 10Hz.

[0057] Turn on the standard solar simulator to set the light intensity to irradiate the perovskite solar cell, and simultaneously start the data recording function of the high-precision multimeter to record the change data of the terminal voltage of the button double-layer supercapacitor over time within 200 seconds, and obtain the charging voltage versus time curve.

[0058] Table 1. Scattered data of photovoltaic characteristics and energy storage test in Example 1: According to Table 1 and Figure 1 and Figure 2 The data shows that the perovskite solar cell prepared in Example 1 generates photogenerated carriers under illumination. The output current density and output power density form a closed working range as the scanning voltage changes. In the closed loop state, the terminal voltage of the coin double-layer supercapacitor shows a nonlinear increasing trend with illumination time, and then tends to stabilize at the charging threshold. The test results show that the photoelectric conversion process of the perovskite solar cell and the charge storage process of the coin double-layer supercapacitor are not affected by the processing technology. The reverse process sequence combined with the low-temperature curing silver paste electrical connection blocks the dissolution of the insulating parts of the electronic components by polar solvents and avoids the degradation of perovskite phase transition caused by high temperature environment, realizing the physical and chemical isolation and electrical connection between heterogeneous devices.

[0059] Test Example 2: The complete system prepared in Example 1 was placed on the central workbench of an environmental darkroom equipped with a programmable LED light source assembly, ensuring that the light emitted from the light source uniformly covered the perovskite solar cell area on the surface of the system.

[0060] The first voltage probe lead of the multi-channel oscilloscope is connected in parallel to the bus node of the system power management chip input terminal, i.e., the two ends of the button double-layer supercapacitor, to monitor the system bus voltage.

[0061] The high-frequency current probe is clamped onto the feed line loop connecting the internal wireless communication module to the radio frequency transmitting antenna, and set as the second monitoring channel of the oscilloscope to record the current pulse characteristics during radio frequency signal transmission.

[0062] The lighting control program for the ambient darkroom was edited on the host computer, and the lighting intensity was set to evolve in a stepwise manner over time: maintaining 0 mW / cm² for 0 to 100 seconds. 2 No light, 100 to 250 seconds, set to 20mW / cm 2 In low light, the power output increases to 80mW / cm² after 250 to 400 seconds. 2 Strong light, drops back to 0mW / cm² in 400 to 600 seconds. 2 Light out.

[0063] Start the dual-channel continuous trigger acquisition mode of the oscilloscope, run the illumination evolution program of the dark box synchronously for 600 seconds, and export the discrete sampling data of voltage and current corresponding to the two channels.

[0064] Table 2 Discrete Data Table of Bus Voltage and Operating Status Distribution in Example 1: According to Table 2 and Figure 3 and Figure 4 The data shows that when the system experiences different lighting environments, each state transition node strictly follows the pre-configured multi-level threshold control logic. Before the bus voltage is charged to 2.7V under weak light, the system does not experience premature power-on. After exceeding the 2.7V threshold, the circuit closes to generate a pulse operating current. During the light-off discharge phase, the bus voltage drops from a high level. When it crosses 2.7V, the communication module continues to transmit data pulses until the voltage drops to trigger the 2.3V power-off threshold, after which it enters deep sleep. The test results demonstrate the state machine flip logic composed of the first set threshold, the power-off threshold, and the restart threshold. This verifies the buffer energy margin built at the hardware physical level by the 0.4V voltage hysteresis, enabling the node to eliminate frequent restarts and abnormal resets of the system at critical light boundaries such as dusk or rain, ensuring the adaptive adjustment stability of IoT micro-energy management.

[0065] Test Example 3: The systems prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were placed on a test bench, and the perovskite solar cell areas on the surface of the systems were irradiated using a standard solar simulator, with the light intensity calibrated to 100 mW / cm². 2 .

[0066] The output electrodes of the perovskite solar cells of each system are connected to the measurement channel of the digital source meter using a conductivity test fixture. The scanning voltage range is set to -0.1V to 1.2V. The voltage scanning program is run and the output current is recorded. The host computer of the digital source meter calculates the photoelectric conversion efficiency and fill factor of each test object and outputs the corresponding IV characteristic curve.

[0067] Disconnect the system from the digital source meter, remove the light source from the test environment, and use a high resistance meter to connect the two test probes to the power bus pin and ground pin of each system power management circuit, respectively. Apply a 5V DC test voltage, keep the voltage constant for 15 seconds, and record the insulation resistance value at this time.

[0068] For adjacent data communication pins in the circuit control section, use the continuity and resistance measurement settings of a high-precision multimeter to detect the electrical connection status between the pins and record the circuit distribution insulation characteristics of each test object.

[0069] Table 3 Summary of photovoltaic performance and electrical insulation parameters of Example 1 and each comparative example: According to Table 3 and the appendix Figure 5 and attached Figure 6 The data shows that the processing conditions have a clear impact on the system integration and functional integrity. Comparing the photovoltaic output characteristics of Example 1 and Comparative Example 2, Comparative Example 2 uses a conventional 250℃ reflow soldering process, which causes the perovskite material to undergo phase transition degradation due to heat, and the IV characteristic curve tends to be resistive, with the photoelectric conversion efficiency dropping to 0.03%. In contrast, Example 1 uses low-temperature curing to keep the thermal tolerance range of the functional layer within the safe range. Comparing the insulation impedance data of Example 1 with Comparative Examples 1 and 3, no physical isolation protection or reversed manufacturing sequence was implemented. At that time, the polar aprotic solvent caused severe corrosion to the circuit conformal coating and pins, causing the insulation impedance to drop sharply from 835.4 MΩ to below the megohm level, and even causing short circuits between pins. At the same time, the height difference of the pre-assembled components in Comparative Example 1 hindered the flattening of the spin-coated liquid film, resulting in a photovoltaic efficiency as low as 3.34%. The results confirmed that the time reversal and physicochemical isolation mechanism of the heterogeneous integration process solves the problems of solvent interference and thermal damage when components are directly mounted on flexible substrates, ensuring the stable operation of the electronic system while maintaining the intrinsic performance of the photoelectric conversion material.

[0070] Test Example 4: The metallized polyimide composite film samples prepared in Example 2 and Comparative Example 4, which have not yet undergone patterning etching, were cut into peel test strips with a width of 3.0 mm and a length of 50 mm using a special cutter according to industry standards.

[0071] Fix one end of the test strip to the lower clamp of the universal tensile testing machine, fix one end of the peeled copper layer to the force sensor on the upper clamp, adjust the clamp to ensure that the peeling angle is maintained at 90°, set the tensile peeling rate to 50 mm / min, start the tensile testing machine, record the tensile load and relative displacement data during the peeling process, calculate and output the continuous peel strength test curve.

[0072] Fine circuit samples after patterning etching and ultrasonic degumming cleaning were selected from Example 2 and Comparative Example 4.

[0073] Using a four-probe tester, 15 test points were randomly selected at equal intervals along the line within a test area with a line width of 100μm. Four probes were pressed onto the surface of the test points, a DC test current of 10mA was applied, and the sheet resistance of each test point was measured and recorded.

[0074] Connect the test probes of the micro-ohmmeter to the two ends of the test circuit of each sample, apply the test voltage to detect the continuity of the circuit, and record the corresponding total continuity resistance value of the circuit.

[0075] Table 4. Discrete data of peel strength and electrical properties test results for Example 2 and Comparative Example 4: According to Table 4 and Appendix Figure 7 and attached Figure 8 The data shows that Comparative Example 4, which did not introduce an adhesive layer, and Example 2, which introduced titanium as a metal adhesive layer, differed in peel strength and electrical properties. The tensile peel strength of Comparative Example 4 remained in the extremely low load range, and after undergoing wet etching and ultrasonic debonding processes, the sheet resistance dispersion of the corresponding circuit test points increased, with some node resistance values ​​exceeding the conventional range, and the total conduction impedance of the circuit exhibiting an open circuit state. In Example 2, the peel strength stabilized in the range of approximately 0.88 N / mm, and the sheet resistance values ​​of each test point after etching were concentrated, with the conduction resistance of the entire circuit being 0.42 Ω. The test results indicate that the titanium metal layer improves the bonding state of the copper film on the surface of the polyimide flexible film, and the active metal transition layer has a structural maintenance effect on the resistance of fine circuits to physical stress and chemical cleaning, avoiding circuit breakage failure during the patterning process.

[0076] Test Example 5: The systems of Example 3, Comparative Example 5, and Comparative Example 6 were fixed on the worktable inside the adjustable light environment test chamber to ensure that the test environment temperature was maintained at 25°C.

[0077] Adjust the light source intensity inside the test chamber to the set weak illumination level so that the charging current generated by the photovoltaic area of ​​the three systems is slightly less than the average operating current when the 32-bit ultra-low power single-chip microcomputer is woken up to execute radio frequency transmission, thus establishing a critical power supply state.

[0078] The voltage test terminals of the multi-channel data acquisition instrument are connected in parallel to the bus test nodes of the three systems, namely the input terminals of the power management chip and the two poles of the button double-layer supercapacitor. The sampling frequency is set to 10Hz, and the system bus voltage data is continuously recorded.

[0079] A matching radio frequency signal receiving base station and terminal statistics host computer are deployed outside the environmental test chamber, and relevant protocols are configured to establish data communication links with each test system.

[0080] Turn on the light source and testing equipment, and let the three systems run continuously for 3 hours under the set weak light conditions.

[0081] After the test, the system bus voltage timing data stored in the data acquisition instrument is exported; the success rate of data packets sent by each system during operation is extracted by the host computer through the terminal, and the total number of abnormal resets recorded by the underlying registers of the 32-bit ultra-low power single-chip microcomputer is read.

[0082] Table 5. Statistical test data of the operating characteristics of Example 3 and each comparative example under the weak light critical state: According to Table 5 and Appendix Figure 9 and attached Figure 10 The data shows that under the critical state of weak light where the photovoltaic charging current is insufficient to maintain the continuous full-load operation of the system, different levels of control threshold hysteresis settings lead to differences in system stability. In Comparative Example 5, due to the lack of voltage hysteresis, after the bus voltage reaches the threshold and triggers load operation, the voltage of the button double-layer supercapacitor drops instantly below the lower limit of operation, causing the system to cut off power supply and re-accumulate a weak current, exhibiting a high-frequency sawtooth oscillation waveform. This results in thousands of abnormal resets of the 32-bit ultra-low power single-chip microcomputer, with a data packet transmission rate of 0%. In Comparative Example 6, the energy margin provided by the 0.1V hysteresis setting is insufficient to support the power consumption of a single complete RF transmission cycle. The voltage drops below the lower limit midway, causing low-frequency undervoltage repeated restarts, with a transmission success rate of only 6.5%.

[0083] Example 3 uses a 0.6V voltage hysteresis, with the bus voltage exhibiting a long-cycle charge-discharge stepped curve. The hysteresis value constructs a sufficient energy buffer band, ensuring that the system has the energy reserves to complete multiple full data interaction operations after waking up before entering sleep mode. The 32-bit ultra-low power single-chip microcomputer did not experience any abnormal resets during this process, and the communication success rate remained at 100%. The test results show that setting a voltage hysteresis of not less than 0.3V can decouple the contradiction between weak environmental energy input and the transient high power demand of radio frequency transmission at the hardware physical level, eliminating frequent restarts and abnormal resets at the power supply edge of the device.

[0084] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to the equipment structure, process flow, step sequence, operating parameters, or working medium type in these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the disclosed core technical solutions and their equivalent substitutions.

Claims

1. A method for powering Internet of Things (IoT) nodes based on perovskite solar cells, characterized in that, The method includes the following steps: Vinyl-terminated polydimethylsiloxane and polymethylhydrosiloxane crosslinking agent are mixed, degassed, coated onto a carrier plate, and heated and cured to obtain a polydimethylsiloxane elastic buffer layer. A flexible polyimide film is attached to the surface of the elastic buffer layer and vacuum laminated and pressurized to obtain a composite carrier plate that provides flexible buffer support. A metal adhesion layer and a copper layer are sequentially deposited by magnetron sputtering on the surface of the composite substrate. The exposed copper layer and the bottom metal adhesion layer are patterned and stripped by photolithography and wet etching processes to obtain the bottom electrode. A hole transport layer is spin-coated outside the installation area. A perovskite precursor solution composed of lead iodide, methyl ammonium iodide and a mixed solvent is spin-coated and annealed to form a perovskite layer. An electron transport layer, a buffer layer and a silver electrode are then prepared in sequence. An inorganic water-barrier oxygen layer is deposited using atomic layer deposition technology to encapsulate the photovoltaic area. A low-temperature curing silver paste containing flake-shaped micron silver powder and an organic carrier is used to place the power management chip, button-type double-layer supercapacitor, and IoT communication module on the corresponding pads to complete the electrical connection and thermal curing. The output terminal of the perovskite solar cell is connected to the input terminal of the power management chip. The state control logic is configured, and a first set threshold, a second set threshold, a power supply stop threshold, and a restart threshold are set. Combined with the voltage hysteresis set by the system, the operation and sleep modes of the 32-bit ultra-low power single-chip microcomputer are automatically switched to avoid frequent restarts of IoT nodes under critical voltage, and to achieve all-weather self-sustaining power supply.

2. The method for powering IoT nodes based on perovskite solar cells according to claim 1, characterized in that, The polydimethylsiloxane elastic buffer layer comprises the following components in parts by weight: 100 to 150 parts of vinyl-terminated polydimethylsiloxane; and 8 to 10 parts of polymethylhydrosiloxane crosslinking agent.

3. The method for powering IoT nodes based on perovskite solar cells according to claim 1, characterized in that, The perovskite precursor solution is prepared from the following components in parts by weight: 46.1 parts lead iodide; 15.9 to 16.7 parts of methylammonium iodide; 56.6 to 62.9 parts of N,N-dimethylformamide; 7.4 to 18.4 parts of dimethyl sulfoxide.

4. The method for powering IoT nodes based on perovskite solar cells according to claim 1, characterized in that, The low-temperature curing silver paste is made from the following components in parts by weight: 70 to 85 parts of flake-shaped micron silver powder; 15 to 30 parts of organic carrier; wherein the organic carrier is composed of epoxy resin and amine curing agent.

5. The method for powering IoT nodes based on perovskite solar cells according to claim 1, characterized in that, The metal adhesion layer is a titanium layer or a chromium layer; the hole transport layer is an annealed PTAA film; the electron transport layer is a PCBM film; the buffer layer is a thermally evaporated BCP film; and the inorganic water-blocking oxygen layer is an aluminum oxide film.

6. The method for powering IoT nodes based on perovskite solar cells according to claim 1, characterized in that, The steps of mixing vinyl-terminated polydimethylsiloxane with a polymethylhydrosiloxane crosslinking agent, degassing, coating onto a carrier plate, and heating and curing to obtain a polydimethylsiloxane elastic buffer layer, and then attaching a flexible polyimide film to the surface of the elastic buffer layer and performing vacuum lamination and pressure holding to obtain a composite carrier plate providing flexible buffer support include: Stir at 500 to 800 rpm for 10 to 20 minutes, then degas under a vacuum of -0.10 to -0.08 MPa for 15 to 30 minutes; Control the thickness of the coating liquid film to be 100 to 500 μm, and cure it at 80 to 100 °C for 30 to 60 min. Hold the pressure for 10 to 15 minutes at an ambient pressure of 50 to 90 Pa and a membrane pressure of 0.2 to 0.5 MPa.

7. The method for powering IoT nodes based on perovskite solar cells according to claim 1, characterized in that, The steps of spin-coating a hole transport layer outside the mounting area, spin-coating a perovskite precursor solution composed of lead iodide, methyl ammonium iodide, and a mixed solvent, followed by annealing to form a perovskite layer, sequentially preparing an electron transport layer, a buffer layer, and a silver electrode, and then depositing an inorganic water-barrier oxygen layer using atomic layer deposition technology for photovoltaic region encapsulation include: When preparing the perovskite precursor solution, the lead ion concentration of the system is controlled to be 1.2 to 1.5 mol / L, and the solution is separated by filtration after continuous magnetic stirring at 60°C for 2 to 4 hours. The perovskite precursor solution was spin-coated at a speed of 4000 to 6000 rpm, and 100 to 200 μL of chlorobenzene was added dropwise at the center at 10 to 15 s, followed by isothermal annealing at 100 to 110 °C for 10 to 30 min. The inorganic water-barrier oxygen layer with a thickness of 20 to 50 nm is deposited at a temperature of 80 to 100 °C.

8. The method for powering IoT nodes based on perovskite solar cells according to claim 1, characterized in that, The steps of using a low-temperature curing silver paste containing flake-shaped micron-sized silver powder and an organic carrier to place the power management chip, button-type double-layer supercapacitor, and IoT communication module on corresponding pads to complete electrical connection and thermal curing include: The low-temperature curing silver paste was prepared by grinding and dispersing, and the viscosity of the low-temperature curing silver paste at room temperature was controlled to be 20 to 40 Pa·s. Heat and cure in an environment of 60 to 80°C for 30 to 60 minutes.

9. The method for powering IoT nodes based on perovskite solar cells according to claim 1, characterized in that, The steps for fabricating the bottom electrode include: sequentially depositing a metal adhesion layer and a copper layer by magnetron sputtering on the surface of the composite substrate; and then patterning and stripping the exposed copper layer and the bottom metal adhesion layer by photolithography and wet etching processes. The sputtering power of the deposited metal adhesion layer is 50 to 100 W, and the thickness is 10 to 50 nm; the sputtering power of the deposited copper layer is 120 to 150 W, and the thickness is 500 to 2000 nm. The pre-baking temperature in the photolithography process is 90 to 110°C, and the hard film baking temperature is 110 to 120°C.

10. The method for powering IoT nodes based on perovskite solar cells according to claim 1, characterized in that, Connecting the output of the perovskite solar cell to the input of a power management chip, configuring state control logic, setting a first set threshold, a second set threshold, a power-stop threshold, and a restart threshold, and combining this with the system-defined voltage hysteresis, automatically switching the operation and sleep modes of the 32-bit ultra-low-power single-chip microcomputer to avoid frequent restarts of IoT nodes under critical voltage conditions, and achieving all-weather self-sustaining power supply, includes the following steps: The first set threshold is configured to be 3.0 to 3.3V, the second set threshold is configured to be 2.6 to 2.9V, the power supply stop threshold is configured to be 2.2 to 2.3V, the restart threshold is configured to be 2.6 to 2.8V, and the corresponding system set voltage hysteresis is 0.3 to 0.6V; When the power supply voltage is higher than the first set threshold, full power operation or set frequency data acquisition and transmission will be performed. When the supply voltage is between the second set threshold and the first set threshold, the frequency is reduced; When the power supply voltage is lower than the power supply stop threshold, the 32-bit ultra-low power single-chip microcomputer enters undervoltage sleep or deep sleep. When illumination is restored and the power supply voltage rises back above the restart threshold, the 32-bit ultra-low power single-chip microcomputer is reawakened and connected to the load.